2001
DOI: 10.1007/s004140100212
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of disputed single-parent/child and sibling relationships using 16 STR loci

Abstract: This study describes the validation of short tandem repeat (STR) systems for the resolution of cases of disputed parentage where only a single parent is available for testing or where the claimed relationship of both parents is in doubt and also cases where sibship must be tested. Three separate multiplex systems the Second Generation Multiplex, Powerplex 1.2 and FFFL have been employed, giving a total of 16 STR loci. Both empirical and theoretical approaches to the validation have been adopted. Appropriate eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 21 publications
2
22
1
Order By: Relevance
“…In paternity analysis, STRs are a fast and reliable approach and therefore used routinely in many laboratories (e.g. [3,4]), especially since multiplex kits have been developed [5]. In addition, since 2002 a paternity analysis done with only one method, such as PCR, is permitted by the German guidelines for paternity analysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…In paternity analysis, STRs are a fast and reliable approach and therefore used routinely in many laboratories (e.g. [3,4]), especially since multiplex kits have been developed [5]. In addition, since 2002 a paternity analysis done with only one method, such as PCR, is permitted by the German guidelines for paternity analysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Laboratories usually do take into consideration the circumstances of the alleged father or mother, for example, when the alleged father is a close relative of the biological father, such as a brother, father, or uncle (Pu and Linacre, 2007). One study has shown that 3.3% of the genotypes in a sample of 10,000 nephew-uncle pairs completely matched when typed by the Identifiler system (Thomson et al, 2001). Therefore, evaluating these duo cases may lead to false conclusions (Brenner, 1997;Lee et al, 2000;Wenk et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…At least 15 short tandem repeat (STR) loci are being analyzed in nearly all laboratories, and this system is now generally considered sufficient to determine identity or paternity with very high probability of inclusion or exclusion [4,13] In some cases of rape that may have resulted in pregnancy, it is necessary to perform early prenatal paternity analysis. This is most frequently done by testing of chorionic villi or amnionic fluid, but this invasive technique cannot be performed before the 13th week of pregnancy; it is stressful and also bears a small but existing risk for both mother and child.…”
Section: Introductionmentioning
confidence: 99%